DOI: 10.25148/etd.fidc001234
|View full text |Cite
|
Sign up to set email alerts
|

Latina Lesbian Students: Understanding their Experiences and Perceived Sexual Identity Development at a Hispanic-Serving Institution

Abstract: The purpose of this phenomenological study was to explore the experiences of 15Latina lesbian students and their perceived sexual identity development at a predominately Hispanic-serving Institution (HSI). Participants for this study were purposefully selected using criteria, convenience, and snowball sampling.Using a conceptual framework comprised of the four tenets consistent across the spectrum of all sexual identity development models, participants' experiences were described, analyzed, and interpreted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 91 publications
1
7
0
Order By: Relevance
“…For example, studies have universally described the advantages of establishing connections with fellow QPOC (Goode-Cross & Good, 2008;Hill-Silcott, 2015;Revilla, 2010;Vaccaro & Mena, 2011). Wall and Washington (1991), in particular, contended that the presence of QPOC faculty and staff is extremely significant for this student demographic. However, in the absence of other QPOC individuals, queer collegians of color also have been seen to find support with White gay peers (Strayhorn, 2013;Strayhorn et al, 2010;Strayhorn & Mullins, 2012), Black women (Strayhorn, 2013;Strayhorn & Mullins, 2012;Strayhorn & Tillman-Kelly, 2013b), White women (Hill-Silcott, 2015), other people of color regardless of gender (Goode-Cross & Good, 2008), with significant others (Peña-Talamantes, 2013;Strayhorn, 2012b), or with family (Gresham, 2009).…”
Section: Coming Out and Sources Of Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, studies have universally described the advantages of establishing connections with fellow QPOC (Goode-Cross & Good, 2008;Hill-Silcott, 2015;Revilla, 2010;Vaccaro & Mena, 2011). Wall and Washington (1991), in particular, contended that the presence of QPOC faculty and staff is extremely significant for this student demographic. However, in the absence of other QPOC individuals, queer collegians of color also have been seen to find support with White gay peers (Strayhorn, 2013;Strayhorn et al, 2010;Strayhorn & Mullins, 2012), Black women (Strayhorn, 2013;Strayhorn & Mullins, 2012;Strayhorn & Tillman-Kelly, 2013b), White women (Hill-Silcott, 2015), other people of color regardless of gender (Goode-Cross & Good, 2008), with significant others (Peña-Talamantes, 2013;Strayhorn, 2012b), or with family (Gresham, 2009).…”
Section: Coming Out and Sources Of Supportmentioning
confidence: 99%
“…Participants discussed this unique intersection as being conflicting for them" (p. 85). For this reason, Wall and Washington (1991) challenged practitioners to think about the role that religion plays for African Americans and Hispanics. Yet, Chan (2017) and Narui (2011aNarui ( , 2011b) also argued that religion has a similar impact for queer Asian/Asian American students.…”
Section: Complex Individuality Of Qpoc Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have examined college student retention for Black students at community colleges (e.g., Derby & Watson, 2007;Wood, 2012Wood, , 2014Wood & Harris, 2015) and the collegiate experiences of queer and transgender students at community colleges (e.g., Garvey, Taylor, & Rankin, 2015;Ottenritter, 2012;Sanlo & Espinoza, 2012;ZamaniGallaher & Choudhuri, 2011, 2016, including work on racially minoritized queer students at a community college (Whitehead, 2019). For example, Sanlo and Espinoza (2012) provided a list of topic areas to examine and address, including discrimination, health outcomes, and resiliency, as well as to enhance college student retention for queer and transgender students at community colleges.…”
Section: The Case Of Joshuamentioning
confidence: 99%
“…Although researchers have discussed the collegiate experiences of queer and transgender students at MSIs (e.g., Means & Jaeger, 2013;Mobley & Johnson, 2015;Patton, 2011;Patton & Simmons, 2008;Vega, 2016), limited research examines college student retention for Black queer and transgender students at MSIs. In our systematic literature review, we found several articles that focus broadly on college student retention at MSIs (e.g., Brooks & Allen, 2016;Merisotis & McCarthy, 2005;Montgomery & Montgomery, 2012).…”
Section: The Case Of Joshuamentioning
confidence: 99%